1997
DOI: 10.1159/000291840
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the Uterus: Magnetic Resonance Imaging

Abstract: We report the magnetic resonance imaging (MRI) findings with a paramagnetic enhancement agent (gadopentetate dimeglumine (Gd-DTPA)) in a 70-year-old woman with carcinosarcoma of the uterus. In the present patient, the polypoid portion histologically most abundant in the sarcomatous component was strongly enhanced by Gd-DTPA and was clearly demonstrated with high signal intensities on contrast-enhanced Ti -weighted images. We suggest that MRI with Gd-DTPA may be clinically useful for detection of carcinosarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…On T2-weighted images, carcinosarcomas show heterogeneous moderate to high intensity, where the highest intensity represents necrosis and hemorrhage [4,7]. On contrast-enhanced T1-weighted images, carcinosarcoma typically demonstrates heterogeneous enhancement, and although the sarcomatous components of the polypoid portions are often more strongly enhanced than those of adenocarcinoma, necrotic regions of the sarcomatous components show no or weak enhancement [8]. Reflecting sarcomatous components with prominent vascularity, dynamic MRI showed marked enhancement during the early phase and maintained this enhancement to the delayed phase and/or showed gradual and delayed strong enhancement [3].…”
Section: Discussionmentioning
confidence: 99%
“…On T2-weighted images, carcinosarcomas show heterogeneous moderate to high intensity, where the highest intensity represents necrosis and hemorrhage [4,7]. On contrast-enhanced T1-weighted images, carcinosarcoma typically demonstrates heterogeneous enhancement, and although the sarcomatous components of the polypoid portions are often more strongly enhanced than those of adenocarcinoma, necrotic regions of the sarcomatous components show no or weak enhancement [8]. Reflecting sarcomatous components with prominent vascularity, dynamic MRI showed marked enhancement during the early phase and maintained this enhancement to the delayed phase and/or showed gradual and delayed strong enhancement [3].…”
Section: Discussionmentioning
confidence: 99%
“…They did not find any MR features specific to uterine carcinosarcoma and suggested that these characteristics simulated those of invasive endometrial carcinoma. Takemori et al (4) , however, reported a case in which Gd‐DTPA strongly enhanced a polypoid portion within the tumor and suggested that MR with Gd‐DTPA might be clinically useful for diagnosing uterine carcinosarcoma. In the present case, the MR findings were similar to those reported by Worthington et al (2) and Shapeero et al (3) .…”
Section: Discussionmentioning
confidence: 99%
“…Carcinosarcoma may metastasize to pelvic and paraaortic lymph nodes, pelvic soft tissues, the vagina, peritoneal surfaces, and the lungs. These tumors have variable signal intensity on T2-weighted MR images (14). On contrastenhanced images, carcinosarcoma typically demonstrates heterogeneous enhancement, with the polypoid portion of the tumor showing intense enhancement ( Fig 6).…”
Section: Mesenchymal Tumorsmentioning
confidence: 99%